Self-Views and Positive Psychology Constructs Among Second Language Learners in Japan, Taiwan, and the United States - Chen, Xinjie; Lake, J.; Padilla, Amado M. (Frontiers in Psychology, 2020)
The present study is the first to empirically test a hierarchical, positive-oriented model of self and its relationship to the second language (L2) achievement motivation, and compare it in three different cultural contexts of Japan, U.S. and Taiwan. Based on the L2 self model (Lake, 2016), three levels of constructs were developed: Global Self (i.e., Flourishing, Curiosity, and Hope); Positive L2 domain self (i.e., interested-in-L2 self, harmonious passion for L2 learning, and mastery L2 goal orientation); and L2 Motivational Variables (i.e., reading, speaking and listening self-efficacy). A total of 667 students participated in this study, including 181 first-year college students in Japan, 159 high school students in Taiwan, and 327 college students in the U.S. All the participants were learning a L2 in school. Results showed that the measures of positive global self, L2 domain self, and L2 motivational self all had a stronger relationship within their respective levels, and progressively weaker relationships as level of generality/specificity became more distal. Furthermore, the relationships among measures varied in the differing cultural contexts with the Japan-based student participants relatively lower on all measures.